Agricultural Output, Government Expenditure and Economic Growth in Nigeria: A Gregory-Hansen Cointegration Test with Structural Breaks - Salisu, Ali; Adahama Ibrahim, Haladu (European Scientific Journal, ESJ, 2021)
The agricultural sector at large plays a significant role in augmenting economic growth, serves as a source of income to the people, provides food to the teeming population, serves as a source of raw materials to the industries and provides foreign exchange to the country, etc. The current study investigates the short-run and long-run relationship among agricultural output, Government expenditure, and Economic growth in Nigeria using annual time series data from 1985 to 2019. The Zivot-Andrew unit root test indicates that gross domestic product, agricultural output, and exchange rate are stationary at first difference while government expenditure is stationary at level. The Gregory-Hansen test with structural break has confirmed the existence of a cointegration relationship among the variables employed. The Autoregressive Distributive Lag (ARDL) model with break indicates that, in the short-run agricultural output has a negative and statistically insignificant effect on real gross domestic product Nigeria, government expenditure has a positive and statistically significant effect on real gross domestic product in Nigeria, and the exchange rate has a positive and statistically significant effect on real gross domestic product in Nigeria. The break-point coefficient has positive and statistically significant. The long-run result shows that agricultural output has a positive effect on the real gross domestic product in Nigeria, government expenditure has a positive effect on real gross domestic product in Nigeria, and the exchange rate has positive effects on the real gross domestic product in Nigeria. The break coefficient shows positive and statistically significant. The study recommends that the Nigerian government should reduce the lending rate on agriculture and provide incentives to the farmers, this will encourage farmers to borrow and consequently, agricultural output will increase and the Nigerian government should increase its expenditure on agriculture to boost the sector and achieve higher economic growth.